Evaluasi Kebijakan Sosialisasi Penerimaan Mahasiswa Baru Pascasarjana IAIN Kendari - Akib Akib (Institut Agama Islam Negeri (IAIN) Kendari, 2020)
This research uses descriptive qualitative analysis. The purpose of this research is to study how this program can be implemented, the extent to which the program is implemented, the achievement of program objectives as determined, and to look for relationships in the implementation of the program. While the research method used is qualitative research. The evaluation research model used is the DEM (Discrepancy Evaluation Model) Model, a model according to Provus which is also called the Gap Model. This is based on the implementation of the socialization of new student admissions in Islamic economics courses. It is necessary to see the agreement made between the expected results and those that occur in the field as a benchmark to improve the implementation of recruitment. The evaluation results show that the implementation of the socialization policy for admission of new students for the IAIN Kendari postgraduate program has been carried out in accordance with the academic guidelines of the IAIN Kendari and the provisions of the postgraduate IAIN Kendari RKAKL. include: Definition Stage, Installation Stage, Process Stage, Product Stage, Product Comparison Stage Some things that become recommendations to the stakeholders are: 1) Need to develop forms of cooperation with related institutions, especially those related to study permits for civil servants who are in the scope of the Ministry of Religion of Southeast Sulawesi Province, local governments and the business world. 2) Increase the number and competence of lecturers and postgraduate management staff so that they can disseminate effectively to related institutions. 3) Need to prepare sufficient funds to carry out promotions and outreach through print, electronic media, visits to offices and schools and through online information media. 4) Encourage various efforts to conduct socialization by accelerating the issuance of assignments including disbursement of socialization funds prior to implementation of the socialization.Keywords: Socialization Policy, Discrepancy Evaluation Model, Postgraduate